Novel Brain-Stiffness-Mimicking Matrix Gel Enables Comprehensive Invasion Analysis of 3D Cultured GBM Cells - Wang, Shuowen; Wang, Yiqi; Xiong, Jin; Bao, Wendai; Li, Yaqi; Qin, Jun; Han, Guang; Hu, Sheng; Lei, Junrong; Yang, Zehao; Qian, Yu; Dong, Shuang; et al. (Frontiers in Molecular Biosciences, 2022)
Glioblastoma (GBM) is the most common malignant primary brain tumor in adults, which is fast-growing and tend to invade surrounding normal brain tissue. Uncovering the molecular and cellular mechanisms of GBM high invasion potential is of great importance for the treatment and prognostic prediction. However, the commonly used two-dimensional (2D) cell culture and analysis system suffers from lacking of the heterogeneity and in vivo property of brain tissues. Here, we established a three-dimensional (3D) cell culture-based analysis system that could better recapitulate the heterogeneity of GBM and mimic the in vivo conditions in the brain. The GBM cell lines, DBTRG and U251, were cultured by hanging drop culture into GBM multicellular spheroids and embedded in the optimized 3D brain-stiffness-mimicking matrix gel (0.5 mg/ml collagen Ⅰ + 3 mg/ml Matrigel+ 3.3mg/ml hyaluronic acid (HA)). The biochemical composition of the optimized matrix gel is similar to the brain microenvironment and the elastic modulus is close to that of the brain tissue. The dynamic of the GBM spheroids was imaged using high-content imaging for 60 h and four metrics including invasion distance, invasion area, single cell invasion velocity and directionality were employed to quantify the invasion capacity. The result showed that DBTRG cells possess higher invasion capacity than U251 cells, which was consistent with the results of the classic transwell test. Transcriptome analysis of both cell lines was performed to explore the underlying molecular mechanisms. Our novel brain-stiffness-mimicking matrix gel enables comprehensive invasion analysis of 3D cultured GBM cells and provides a model basis for in-depth exploration of the mechanisms regulating GBM invasion including the interaction between GBM cells and brain stroma.